RELATIONSHIP BETWEEN GENDER SOCIALIZATION DONE BY PARENTS AND SEXISM IN ADOLESCENT - Dewi Ashuro Itouli Siregar; Sri Rochani Soesetio (Jurnal Psikologi, 2009)
Based on Social Learning Theory the fact that parent treats their children in different way between their son and daughter is considered as one of the cause of sexism. The aim of this study is to know and to proof the relationship between gender socialization done by parents with sexism in adolescent. The participants of this study are 106 female and 94 male adolescents in DKI Jakarta. The result shows that hostile sexism in male adolescents is higher than female adolescents, and benevolent sexism in female adolescents is higher than male adolescents. Parents also did more traditional gender socialization to female adolescents. There are also correlation between demographic datas such as age, education level and work status in mother and main variable if this study. Another finding is there is no correlation between gender socialization and sexism in male and female adolescents. However, this study finds that gender socialization has a correlation with hostile sexism in male adolescents. This finding will help us to get deeper understanding about the source of sexism.Keywords: sexism, gender sosialization, parents, benevolent, hostile, adolescence, social learning, gender